Do Justice To Court Interpreters In South Africa - Lebese, Samuel Joseph (Stellenbosch Papers in Linguistics Plus, 2014)
Abstract: In South Africa statutory provision governing interpreting norms and standards of practice for court interpreters does not exist. Policy-makers lack knowledge of these norms and standards of practice and have failed to include and define them in any legislation. Court interpreters work without guidance from any policy. The problem is that court interpreters might be seen to be interpreting according to their personal preferences, as each interpreter creates his or her own norms and standards of practice. The aim of this study was to investigate whether there was any statute governing the norms and standards of practice for court interpreters and if not, how the lack thereof can affect their work. This aim was achieved by examining the “Personnel Administration Standard (PAS)” document relating to employment of court interpreters in the Department of Justice and Constitutional Development; the “Magistrates’ Court Act 44 of 1944 (as amended)”; and the “Constitution of the Republic of South Africa, Act 108 of 1996 (as amended)”. The study revealed that the three documents do not mention anything regarding the norms and standards of practice regulating court interpreting in South Africa. The study suggests the need for a statutory provision that will govern and deal with court-interpreting issues in their broadest sense, including norms and standards of practice. Key words: court interpreters, legislation, norms, standards of practice.